Welfare Benefits and Unemployment in Affluent Democracies: The Moderating Role of the Institutional Insider/Outsider Divide - Thomas Biegert (American Sociological Review, 2017)
The effect of generous welfare benefits on unemployment is highly contested. The dominant perspective contends that benefits provide disincentive to work, whereas others portray benefits as job-search subsidies that facilitate better job matches. Despite many studies of welfare benefits and unemployment, the literature has neglected how this relationship might vary across institutional contexts. This article investigates how unemployment benefits and minimum income benefits affect unemployment across levels of the institutional insider/outsider divide. I analyze the moderating role of the disparity in employment protection for holders of permanent and temporary contracts and of the configuration of wage bargaining. The analysis combines data from 20 European countries and the United States using the European Union Labour Force Survey and the Current Population Survey 1992–2009. I use a pseudo-panel approach, including fixed effects for sociodemographic groups within countries and interactions between benefits and institutions. The results indicate that unemployment benefits and minimum income benefits successfully subsidize job search and reduce unemployment in labor markets with a moderate institutional insider/outsider divide. However, when there is greater disparity in employment protection and when bargaining either combines low unionization with high centralization or high unionization with low centralization, generous benefits create a disincentive to work, plausibly because attractive job opportunities are scarce.
Additional information: Dieser Beitrag ist mit Zustimmung des Rechteinhabers aufgrund einer (DFG-geförderten) Allianz- bzw. Nationallizenz frei zugänglich / This publication is with permission of the rights owner freely accessible due to an Alliance licence and a national licence (funded by the DFG, German Research Foundation) respectively.
Keywords: 330; unemployment; welfare state; labor market institutions; institutional interactions; quantitative methods